2005
DOI: 10.1097/01.shk.0000184285.57375.bc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 18 in Nitric Oxide Production and Pancreatic Damage During Acute Pancreatitis

Abstract: The release of the immunomodulator, interleukin 18 (IL-18) into sera early in acute pancreatitis (AP) corresponds to disease severity. IL-18 induces nitric oxide (NO), which is involved in the pathophysiology of pancreatitis. The objective of this study was to clarify the role of IL-18 in pathogenesis and NO production during early AP using recombinant mouse (rm) IL-18 protein and IL-18 gene knockout (KO) mice. After pretreatment with phosphate-buffered saline or rmIL-18, wild-type (WT) or KO mice were injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
2
29
1
Order By: Relevance
“…Therefore, up-regulation of FAS and FASL by IL18 may influence BID activation. IL18 was also required for iNOS IL18 regulates testicular germ cell apoptosis induction, in accordance with the findings of a previous study (Ueno et al 2005). The upregulation of iNOS increases cellular NO levels, which leads to the breakdown of mitochondrial membrane potential and caspase-9 activation (Chan et al 2005).…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, up-regulation of FAS and FASL by IL18 may influence BID activation. IL18 was also required for iNOS IL18 regulates testicular germ cell apoptosis induction, in accordance with the findings of a previous study (Ueno et al 2005). The upregulation of iNOS increases cellular NO levels, which leads to the breakdown of mitochondrial membrane potential and caspase-9 activation (Chan et al 2005).…”
Section: Discussionsupporting
confidence: 76%
“…8 The present study also showed that endogenous IL-18 induced accumulation of neutrophils, iNOS expression, and oxidative stress in the lung. These results are consistent with previously reported evidence; Hesslinger et al showed that iNOS induced neutrophil accumulation and pulmonary edema.…”
mentioning
confidence: 55%
“…7 We also reported that endogenous IL-18 induced iNOS expression during acute pancreatitis in mice. 8 These findings suggest that endogenous IL-18 may relate to accumulating neutrophils and their apoptosis, as well as oxidative stress in acute lung injury.…”
Section: Introductionmentioning
confidence: 94%
“…These cytokines are expressed mainly during the early stages of the disease in serum, pancreas or lungs. Consequently, they may contribute to the disease course only over a brief period of time [15]. In contrast to the profile of these commonly described cytokines, IL-18 expression is delayed.…”
Section: Resultsmentioning
confidence: 99%